A sustainable synthesis of polyhydroxyalkanoate from stubble waste as a carbon source using Pseudomonas putida MTCC 2475 - Kukreti, Neha; Kumar, Pravir; Kataria, Rashmi (Frontiers in Bioengineering and Biotechnology, 2024)
Polyhydroxyalkanoates (PHAs) are biodegradable polymers that can be produced from lignocellulosic biomass by microorganisms. Cheap and readily available raw material, such as corn stover waste, has the potential to lessen the cost of PHA synthesis. In this research study, corn stover is pretreated with NaOH under conditions optimized for high cellulose and low lignin with central composite design (CCD) followed by characterization using Fourier-transform infrared spectroscopy (FTIR), thermal gravimetric analysis (TGA), and scanning electron microscopy (SEM). Design expert software performed further optimization of alkali pretreated corn stover for high total reducing sugar (TRS) enhancement using CCD using response surface methodology (RSM). The optimized condition by RSM produced a TRS yield of 707.19 mg/g. Fermentation using corn stover hydrolysate by Pseudomonas putida MTCC 2475 gave mcl-PHA detected through gaschromatography–tandemmassspectrometry (GC-MS/MS) and characterization of the PHA film by differential scanning calorimetry (DSC), FTIR, and nuclear magnetic resonance (NMR). Thus, this research paper focuses on using agriculture (stubble) waste as an alternative feedstock for PHA production.